Depression symptoms of primary school students from the fourth and seventh grades - Agnieszka Lewicka-Zelent; Agnieszka Pytka; Sylwia Huczuk-Kapluk; Kazimierz Nosal (Studia z Teorii Wychowania)
The adolescent period is indicated as one of the risk factors responsible for depression symptoms. In Poland the attention has been drawn to this problem relatively rarely as it was hitherto stereotypically perceived as the disease of the elderly. However, school psychologists and counselors more and more frequently suggest that their students exhibit different symptoms characteristic of, among others, youth depression. Thus, authors’ objective consisted in conducting a pilot study in order to check if there are any reasons for distress as to the psychophysical state of primary school students. The study was carried out in the group of one hundred and forty (140) students from the fourth and seventh grades where the biggest teaching changes occurred and one hundred and forty (140) parents and class teachers. Children’s Depression Inventory (CDI) by Maria Kovacs was employed in research. Based on the obtained research results one may put forward the thesis that there is a necessity to conduct in-depth diagnostic studies oriented towards revealing children’s and school youth’s depression symptoms.